Indo-Anglian: Connotations and Denotations - Sharma, Susheel Kumar; Шарма, Сушіл Кумар (My University, 2018)
different name than English literature, ‘Anglo-Indian Literature’, was given to the body of literature in English that emerged on account of the British interaction with India unlike the case with their interaction with America or Australia or New Zealand. Even the Indians’ contributions (translations as well as creative pieces in English) were classed under the caption ‘Anglo-Indian’ initially but later a different name, ‘Indo-Anglian’, was conceived for the growing variety and volume of writings in English by the Indians. However, unlike the former the latter has not found a favour with the compilers of English dictionaries. With the passage of time the fine line of demarcation drawn on the basis of subject matter and author’s point of view has disappeared and currently even Anglo-Indians’ writings are classed as ‘Indo-Anglian’. Besides contemplating on various connotations of the term ‘Indo-Anglian’ the article discusses the related issues such as: the etymology of the term, fixing the name of its coiner and the date of its first use. In contrast to the opinions of the historians and critics like K R S Iyengar, G P Sarma, M K Naik, Daniela Rogobete, Sachidananda Mohanty, Dilip Chatterjee and Gayatri Chakravorty Spivak it has been brought to light that the term ‘Indo-Anglian’ was first used in 1880 by James Payn to refer to the Indians’ writings in English rather pejoratively. However, Iyengar used it in a positive sense though he himself gave it up soon. The reasons for the wide acceptance of the term, sometimes also for the authors of the sub-continent, by the members of academia all over the world, despite its rejection by Sahitya Akademi (the national body of letters in India), have also been contemplated on. Завдяки взаємодії англійської літератури з Індією, на відміну від її взаємодії з Америкою, Австралією або ж Новою Зеландією, утворився новий шар англій-ської літератури, який отримав назву: англо-індійська література. Спочатку навіть літе-ратурні доробки індійців (переклади, а також художні твори англійською мовою) були класифіковані під заголовком «англо-індійські», але згодом їх було перейменовано на «індо-англійські», зважаючи на зростаюче розмаїття та обсяг написаних індійцями творів англійською мовою. Проте на відміну від попереднього, останній не знайшов прихильності серед укладачів англійських словників. Із часом чітка лінія демаркації, окреслена на підставі предмета та погляду автора твору, зникла, і сьогодні навіть англо-індійські тексти класифікують як індо-англійські. Крім огляду різних конотацій терміна «індо-англійці», у статті проаналізовано такі проблеми: етимологія терміна, фіксація імені його автора і дата першого використання. На відміну від думок істориків та критиків, таких як К Р С Ієнґар, Г П Сарма, М К Наік, Даніела Роґобете, Сачідананда Моганті, Діліп Чаттерджі та Ґайатрі Чакраворти Співак, стверджувалося, що термін «індо-англійці» вперше було використано в 1880 р. Джеймсом Пейном для покликання на твори індійців англійською мовою радше в зневажливому тоні. Однак Ієнґар використовував цей термін в позитивному значенні, хоча й він сам невдовзі від нього відмовився. У статті також проаналізовано причини широкого прийняття цього терміна, іноді навіть авторами субконтиненту, членами наукових кіл у всьому світі, незважаючи на те, що «Сагітья Академі» (Національна академія літератури Індії) від нього відмовився.
Індо-англійська: конотації та денотації
Keywords: Anglo-Indian; Indo-Anglian; literary history; Indo-English; англо-індійська; індо-англійська; історія літератури